1989
DOI: 10.1016/0735-1097(89)90511-1
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of right ventricular anatomy and function by quantitative radionuclide ventriculography

Abstract: Determination of right ventricular ejection fraction and volumes from radionuclide studies is cumbersome and is subject to considerable methodologic error. Further, assessment of regional wall motion has only infrequently been approached in a systematic way. A system of right ventricular ejection fraction and volume measurements is described that utilizes the previously validated single plane geometric method applied to first pass radionuclide angiocardiograms. Five right ventricular chords were defined and us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
3

Year Published

1993
1993
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(8 citation statements)
references
References 15 publications
1
4
0
3
Order By: Relevance
“…Another study using cine-ventriculography reported that the group with DCM had a larger RV end-diastolic volume index, and higher RV end-diastolic and mean pulmonary artery pressures than the control group, 13 which differs from our results, probably because some of their cases with DCM were not taking medication or did not have a lower RVEF than LVEF despite there being no obvious sign of RV dysplasia in an endomyocardial biopsy. A study using first pass radionuclide angiography reported that the group with DCM with typical symptoms and signs of congestive heart failure had a larger RV end-systolic volume index and a lower RVEF than the control group, and that there were no significant differences in the RV end-diastolic volume index between the 2 groups, 14 which are comparable results to ours. We presume that differences in the degree of RV volume load (the level of preload in the RV) or the extent of RV myocardial damage underlie the differences in the results among the studies.…”
Section: Right Ventricular Volume In Dcmsupporting
confidence: 81%
“…Another study using cine-ventriculography reported that the group with DCM had a larger RV end-diastolic volume index, and higher RV end-diastolic and mean pulmonary artery pressures than the control group, 13 which differs from our results, probably because some of their cases with DCM were not taking medication or did not have a lower RVEF than LVEF despite there being no obvious sign of RV dysplasia in an endomyocardial biopsy. A study using first pass radionuclide angiography reported that the group with DCM with typical symptoms and signs of congestive heart failure had a larger RV end-systolic volume index and a lower RVEF than the control group, and that there were no significant differences in the RV end-diastolic volume index between the 2 groups, 14 which are comparable results to ours. We presume that differences in the degree of RV volume load (the level of preload in the RV) or the extent of RV myocardial damage underlie the differences in the results among the studies.…”
Section: Right Ventricular Volume In Dcmsupporting
confidence: 81%
“…Right ventricular regional wall motion has been assessed by cineangiography, 19-21 2-D echocardiography, 5,22 radionuclide angiography 23 and magnetic resonance imaging, 24 but none of these reports examined the direct relation between the right ventricular global ejection fraction and regional shortening. Our results suggest that the ejection function of the right ventricle can be evaluated to some degree by the % shortening of the SF dimension in cases without obvious regional wall motion abnormalities of the left ventricle or right ventricular overload.…”
Section: F-mp Distance From the Right Ventricular Free Wall To The Mmentioning
confidence: 99%
“…The ability to visualize both the right and left ventricles has proven difficult in prior studies using exercise radionuclide, echocardiographic and earlier CT imaging techniques [23][24][25]. Poor visualization of the right ventricle, a poorly defined endocardial surface, irregular right ventricular geometry, and limited reproducibility of exercise studies are important limitations of echocardiography in evaluating the left and right ventricle [26].…”
Section: Discussionmentioning
confidence: 99%